Destination image evolvement through experiential marketing / Nor Aminin Mohd Khalid, Rosmimah Mohd Roslin - Mohd Khalid, Nor Aminin; Mohd Roslin, Rosmimah (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2016)
This qualitative study is an exploratory attempt at understanding destination image through the writings of the travel writers who have undergone the familiarisation or fam programs organised by Tourism Malaysia. The idea behind the program is for the writers to experience first-hand specific destinations in Malaysia and then expressed their experiences through their travel writings. The data in the form of the travel articles were collected with the assistance of Tourism Malaysia based on the suggested criteria established. This study established that it was possible to derive destination image by interpreting the depth of the articles and through the expressions of the travel writers who very often narrated their experiences coherently through vivid depictions and emotions. It is suggested that future studies further test the evolving themes through empirical analyses that are more conclusive and statistically proven.